Ekonomski pristop določanja upoštevnega trga v konkurenčnem pravu EU - Repas, Martina (LeXonomica, 2021)
Use of economics in defining relevant market in EU competition law. Authoress deals with the rules of defining relevant market in EU competition law as very important tool in taking decision weather an undertaking restricts effective competition. For this purpose qualitative and quantitative methods of defining relevant market are analysed including the advantages and disadvantages of both. Authoress stresses that qualitative methods such as product characteristics, their prices and intended use are not in accordance with the modern economic approach which nowadays dominates in EU competition law. Their use should be restricted only to the situations where economic (quantitative) methods (such as SSNIP test, price correlation, co- integration analysis etc.) cannot be used due to the lack of relevant data.Povzetek. Avtorica obravnava pravila oz. metode določanja upoštevnega trga za namene uporabe pravil konkurenčnega prava EU, ki je pomembno orodje pri ugotovitvi ali podjetja učinkovito omejujejo konkurenco na trgu. Pri tem analizira obe tehniki določanja upoštevnega trga - kvantitativno in kvalitativno - ter navaja prednosti in slabosti obeh. Avtorica izpostavlja, da kvalitativne tehnike določanja, ki se nanašajo na fizične značilnosti proizvodov, namen uporabe, razlik v cenah ipd. niso v skladu z modernim ekonomskim pristopom, ki danes dominira v konkurenčnem pravu EU. Upoštevale naj bi se predvsem v situacijah, ko ekonomskih (kvantitativnih) tehnik, kot so SSNIP test, cenovna korelacija. analiza ko-integracije idr. ni mogoče uporabiti zaradi pomanjkanja relevantnih podatkov.
Keywords: competition law; relevant market; demand-side substitution; supply-side substitution; SSNIP test; cellophane fallacy; cross-price elasticity; price correlation; co-integration analysis